2018
DOI: 10.1073/pnas.1804437115
|View full text |Cite
|
Sign up to set email alerts
|

Rates of cavity filling by liquids

Abstract: Understanding the fundamental wetting behavior of liquids on surfaces with pores or cavities provides insights into the wetting phenomena associated with rough or patterned surfaces, such as skin and fabrics, as well as the development of everyday products such as ointments and paints, and industrial applications such as enhanced oil recovery and pitting during chemical mechanical polishing. We have studied, both experimentally and theoretically, the dynamics of the transitions from the unfilled/partially fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 27 publications
(22 reference statements)
0
33
0
Order By: Relevance
“…To date, few publications discuss time dependent wetting based on the Cassie-Wenzel transition 26,27 for the viscous fluids, so this issue is left for future work. Also, it is needed for future studies to investigate wetting transitions in new factors such as the dissolution of the entrapped gas into the liquid, effects of mechanical vibrations, and breakthrough pressures 28,29 .…”
Section: Resultsmentioning
confidence: 99%
“…To date, few publications discuss time dependent wetting based on the Cassie-Wenzel transition 26,27 for the viscous fluids, so this issue is left for future work. Also, it is needed for future studies to investigate wetting transitions in new factors such as the dissolution of the entrapped gas into the liquid, effects of mechanical vibrations, and breakthrough pressures 28,29 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to quantitatively relate the progress of wetting transition to time, Arrhenius equation with an activation energy being the adhesion energy is used in a recent study by Seo et al 31 .…”
Section: Time-dependent Wetting Transition Modelmentioning
confidence: 99%
“…The typical time for wetting transition to complete ranges from seconds to days, depending on the aforementioned factors and liquid properties, including interfacial tension and viscosity. [28][29][30][31] It has been also found that hierarchical surface structure can dramatically increase the stability of the Cassie state, slowing the transition [46][47][48] . On the other hand, external excitations, such as vibration can help overcome the energy barrier, accelerating the wetting transition [49][50][51] .…”
Section: Introductionmentioning
confidence: 99%
“…These bio‐inspired [ 18,23 ] microtextures are known as doubly reentrant cavities (DRCs), and they can entrap air inside them on immersion in liquids due to their topography, regardless of their surface make‐up. [ 21 ] In fact, the transition of these air‐filled cavities—Cassie‐states [ 24–26 ] to the fully‐filled or the Wenzel‐state [ 27 ] depends on a number of factors, such as the compressibility of the trapped air, liquid vapor pressure, capillary condensation, the solubility of the trapped air in the liquid, and the cavity geometry. [ 20 ] For instance, when hexadecane (vapor pressure at NTP, P V = 0.01 kPa) was used to immerse silica surfaces adorned with circular DRCs (apparent advancing contact angle on flat silica, θ A ≈ 20°), they robustly entrapped air, which remained intact even after 27 days.…”
Section: Introductionmentioning
confidence: 99%